Linguocultural and Linguopragmatic Features of the Concept of “Hospitality” in English and Uzbek: An AI-Assisted Comparative Analysis - Najmiddinova, Mekhrigul Najmiddin qizi (The Lingua Spectrum, 2026)
This study investigates the linguocultural and linguopragmatic features of the concept of “hospitality” in English and Uzbek through an AI-assisted comparative framework. Hospitality, as a universal yet culturally specific value, is encoded distinctly across different languages and cultural systems. In Uzbek, the concept of mehmondo‘stlik functions as a deep moral and communal obligation, richly expressed through proverbs, phraseological units, and obligatory speech acts of insistence and generosity. In English, hospitality is predominantly framed within politeness strategies and optional generosity, governed by face-saving mechanisms and individual autonomy norms. Employing AI-assisted corpus analysis alongside traditional linguocultural and linguopragmatic methods, this research identifies key cross-cultural divergences in conceptual framing, speech act realization, and idiomatic encoding. The findings reveal that Uzbek hospitality discourse is characterized by collective duty and proverb-backed imperatives, while English hospitality discourse foregrounds individual courtesy and pragmatic flexibility. These contrasts carry significant implications for intercultural communication, translation studies, and language pedagogy.